(untitled) (Archaeologia Adriatica, 2009)
A fish-shaped relief glass bottle was found in grave 59 (quadrant 3A) during the rescue archaeological excavations at the site of Trgovački Centar (Shopping Mall) Relja in 2005. This find is particularly important since the entire context of the find is defined so that it offers valuable insights about the distribution of this type of the bottle as well as about the the chronological determination of its formation which has been a subject of discussions. These chronological dilemmas were solved by grave goods and typology of the burial at the ancient necropolis of Iader. On the basis of glass finds which belonged to grave goods from grave 59 together with the fish-shaped relief bottle we can state with certainty that this bottle which was blown into a two-part mold was made in the period from the mid-first to the beginning of the second century AD, to be precise in the second half of the first century AD. Out of total number of eight examples of these bottles, place of discovery is known for only four (Romania, Greece and Croatia), two of which were found in the Croatian littoral. Since none of the findspots was located in the western part of the Roman Empire, one cannot help thinking that fish-shaped relief bottles were created in the eastern Mediterranean, most likely in the Syrian glassmaking workshops in the first century AD when small Syrian relief bottles in vegetal and anthropomorphous shapes with relief decoration were very popular.